Structure and electronics in dimeric boron π expanded azine and salphen complexes. Issue 5 (28th February 2017) - Crandall, Laura A.; Dawadi, Mahesh B.; Burrell, Tailon; Odoom, Adwoa; Ziegler, Christopher J.
Abstract : We present the synthesis and photophysical properties several π expanded dimeric boron chromopohres, incorporating both bis(2-hydroxynaphthaldehyde)azine as well as ortho, meta and para variants of the analogous 2-hydroxynaphthaldehyde salphen compounds. Abstract : Although boron-based fluorophores incorporating nitrogenous chelating ligands have received much attention, there has been little work on examples of boron–salphen and azine derivatives. In this report, we present several π expanded boron salphen type complexes, incorporating both bis(2-hydroxynaphthaldehyde)azine as well as ortho, meta and para variants of the analogous 2-hydroxynaphthaldehyde salphen compounds. For the azine, we observed only the formation of a single BF2 adduct, while for the naphth-phen compounds dimeric BF2 binding was observed. All new compounds were fully characterized via X-ray diffraction, and both DFT and TDDFT studies were carried out to probe the electronic structures of these fluorophores.